The function and formal dynamic of the typical stories in high buildings - A. Alshamari, Haitham A.; Mousa, Zahraa M. (Nahrain University College of Engineering Journal, 2017)
Sees that the essence of the formation and the high building production based to the function, which in turn affected and changed levels by change the shape of building at any moment of the vertical and horizontal extending, and most of this, the high buildings has seen formative developments, especially in multi floors, structure, capacity of spaces, and functions for those floors that recognized by the first beginnings of high buildings forms. These developments mostly been grader to produce sculptural forms make them different from traditional high buildings, that this formality change effect in the level of function and their types or at the level of the comparison between the building floors itself and extended over to the building performance and their urban integration. Thus crystallize the research problem in the lack of studies which dealt the efficiency of high buildings formation, which in turn formed the intercalation phenomena on the cities, without any common features between them and the fabric of the city, and with the horizontal towers.The create dynamic formalities creates rearrange the four varieties function (usability - structural - Environmental - Iconic), thus creating a functional dynamic that rearranges the levels of dominance function on those changing floors , so the search was divided into three sections are:1 - Function and their types. 2 - Performing and dynamic formal and urban integration. 3 - practical study of a global project (Norman Foster), and three proposed architectural projects for architecture students /AL-Nahrain University / 2013.Thus the research adopted on two hypotheses, the first: that the four function are mainly in the form of high buildings production, and the second: that the formal change of the building floors involves a functional change, according to the previous classifications.Research benefit lies in: - Strengthening go towards the high buildings that have strong function and form, thought full in terms of mutual changes. - Evaluation the projects for proposed high buildings. - Call to raise the performing efficiency and urban integration.